Not quite Pott's puffy tumour. (25th April 2018) - Misirovs, Rasads; Gohil, Rohit; Ross, Peter; Manickavasagam, Jaiganesh
Abstract : Pott's puffy tumour (PPT) is characterised by a subperiosteal abscess associated with osteomyelitis of the frontal bone—a rare complication of frontal sinusitis, more common in the paediatric population. We describe a case mimicking PPT, where abscess extension was facilitated by previous surgery. Usually patients with PPT would be systemically unwell, but our patient, a 63-year-old Caucasian man, was systemically well with a large swelling of his forehead. A CT was performed to evaluate possible intracranial and intracerebral complications such as epidural, subdural and brain abscesses. Emergent surgical drainage was performed with prolonged administration of antibiotic therapy. 12 weeks later, he had recollection in the frontal sinus requiring incision and drainage. 6 weeks afterwards, he underwent planned Lothrop procedure and endoscopic sinus surgery. Although clinically the patient presented with overwhelming features of PPT, we emphasise that PPT involves osteomyelitis of frontal bone, which is absent in our case.